Targeting C1q signaling in fibro-adipogenic progenitors prevents regenerative fibrosis of aged muscle - Abhijnya Kanugovi; Paola Aguiari; Rachel Choi; Soochi Kim; Di Wu; Antoine de Morree; Summer Bui; Richard Lam; Stefano Biressi; Ling Liu; Thomas A. Rando (Proceedings of the National Academy of Sciences, 2026)
Skeletal muscle fibrosis, as occurs with age, in response to injury, or in the setting of degenerative diseases, results in impairments of muscle regeneration and function. Fibro-adipogenic progenitors (FAPs), a distinct population of muscle-resident mesenchymal progenitor cells that reside in the muscle interstitium, play a crucial role in normal muscle regeneration by supporting muscle stem cell proliferation. However, in pathological conditions such as severe or recurrent muscle injury, FAPs can aberrantly differentiate into fibrogenic cells, resulting in excessive deposition of extracellular matrix and fibrosis. In this study, we explore the molecular regulation of FAP differentiation along the fibrogenic lineage to gain insights into the mechanisms of fibrosis in aged muscle in response to injury. Our findings reveal that aging is associated with an increased expression of the complement component 1q (C1q) in muscle-resident macrophages and elevated expression of the complement proteins C1r and C1s in FAPs. Exposure of proliferating FAPs to C1q results in the activation of the Wnt signaling pathway, elevated expression of collagen genes, and FAP fibrogenic differentiation, leading to increased tissue fibrosis. We demonstrate that either pharmacological inhibition of the complement pathway or genetic ablation of C1s in FAPs in aged mice reduces fibrogenic differentiation of FAPs by suppressing Wnt signaling. This reduction in FAP differentiation attenuates the fibrotic response to injury in aged animals as well as in a mouse model of muscular dystrophy. Our study supports the inhibition of complement signaling as a potential therapeutic strategy for mitigating fibrosis in skeletal muscle injury or degeneration.